CNS Plasmacytoid Dendritic Cells Regulate the Severity of Relapsing Experimental Autoimmune Encephalomyelitis - Bailey-Bucktrout, Samantha L. (2008)
Plasmacytoid dendritic cells (pDC) have both stimulatory and regulatory effects on T cells. pDCs are a major CNS-infiltrating DC population during experimental autoimmune encephalomyelitis (EAE), but unlike myeloid DCs (mDC) have a minor role in T cell activation and epitope spreading. We show that depletion of pDCs during either the acute or relapse phases of EAE resulted in exacerbation of disease severity. pDC depletion significantly enhanced CNS but not peripheral CD4(+) T cell activation, as well as IL-17 and IFN-γ production. Moreover, CNS pDCs suppressed CNS mDC-driven production of IL-17, IFN-γ and IL-10 in an IDO-independent manner. The data demonstrate that pDCs play a critical regulatory role in negatively regulating pathogenic CNS CD4(+) T cell responses highlighting a new role for pDCs in inflammatory autoimmune disease.